Alcohol Consumption Among Spanish Female Adolescents: Related Factors and National Trends 2006–2014 - Alonso-Fernández, Nazaret (Int J Environ Res Public Health, 2019)
Background: The purpose of this study was: (a) to estimate trends over time in the prevalence of alcohol consumption among female adolescents between 2006 and 2014; (b) to identify the factors associated with the probability of consuming alcohol during this period for Spanish female adolescents (14–18 years old). Methods: Spanish nationwide, epidemiological, cross-sectional study on alcohol consumption by adolescent women. We used individualized secondary data retrieved from the 2006 and 2014 Spanish state survey on drug use in secondary education, for a total of 48,676 survey respondents aged 14 to 18 years. Alcohol use was the dependent variable. We also analyzed sociodemographic and educational features, lifestyle habits, perceived health risk for consumption, and perceived availability of substance using logistic regression models. Results: The prevalence of alcohol consumption among female adolescents was 62.35% during the study period. Alcohol consumption increased with age and was more frequent on weekends than on school days. The variables associated with a greater probability of alcohol consumption were tobacco, marijuana (aOR = 2.37; 95% CI: 2.08–2.72), and alcohol consumption by friends (aOR = 7.24; 95% CI: 6.42–8.16). Conclusions: Alcohol consumption by female adolescents in Spain significantly increased from 2006 to 2014. Marijuana and alcohol consumption by friends were associated factors.